The last stage of ''kulak" extermination in the Soviet Union (1945-1952) - Šaškov, Viktor (Lietuvos istorijos studijos, 1997)
The extermination of "kulaks," i.e., the last stage of village expropriation, exile of wealthy farmers to Siberia or other distant regions of the Soviet Union was a part of the "Socialism creation" programme. The author reviews in brief the process of "kulaks" extermination and exile in terms of social aspects until the Germany-USSR war. The greatest emphasis is put on the last fourth stage of the process mentioned with the involvement of the Lithuanian village. It was estimated that 28,521 families, i.e., 99,336 people from Lithuania, were exiled to Siberia during the period 1945-1951. At that time, the peasants from Latvia, Estonia, Moldavia, Pskov region (Latvian districts), Beloruss (West part), Izmail region, and even Middle Asia were exiled to Siberia, but the biggest part (half of them) was comprised by the Lithuanian farmers. Referring to the Moscow archives, the author makes an attempt to reveal the mechanism of exile and answer the question concerning different figures on exiled people given in various official documents of that time. Everyday life and working conditions of exiles are also briefly discussed. The exiles from Lithuania are considered in the context of general statistics of all Soviet socially-based exiles.
Keywords: -